Wüstungsschema und Wüstungsquotient - Born, Martin (ERDKUNDE, 1972)
The geographical study of village abandonment has, since K. Scharlau (1933) presented his 'abandonment schema', refined its problem formulation and methods. In addition, its spheres of interest have been extended to include in the last few decades not only village abandonment but also a stronger attention to the abandonment of farmland. With the study of temporary abandonment and of settlements which have disappeared although the farmland is still used, abandonment research has taken up questions of settlement genesis in the recent period and of research into field pat terns. Because of this an extension of the 'abandonment schema' which is currently limited to permanent abandonment of settlements and farmland is unavoidable. It is necessary to include in the schema settlements and fields which are given up for only a short time (I n t e r i m s w ü s t u n g e n) and those abandonments which, after a longer period, come back into use (t e m p o r ä r e W ü s t u n g e n). Apart from these, abandonment of formerly agriculturally used areas (F l u r w ü s t u n g e n) should be contrased, in the abandonment schema, with those lands of abandoned villages which are in fact still used (W ü s t u n g s f l u r e n). At the moment its is not possible to include within the 'abandonment schema', developed for rural settlements, any settlements or installations of a commercial or industrial character. Attempts to do so have not yet led to satisfactory results. The extent of the phenomenon of abandonment can at least be approximately indicated by the 'abandonment quotient'. Of course the abandonment quotient is not merely intended to indicate the percentage of the villages of the late Middle Ages which had been abandoned by the end of the period of abandonment. It should be treated as a formula in which temporary abandonments should also be quantatively included; in addition, the period of time for which the 'abandonment quotient' is relevant should be given.